177k views
5 votes
X = 2y + 18
5x = -3y - 27

Use the substitution method to solve the system below

X = 2y + 18 5x = -3y - 27 Use the substitution method to solve the system below-example-1

1 Answer

3 votes

Answer:

(0, - 9 )

Explanation:

x = 2y + 18 → (1)

5x = - 3y - 27 → (2)

substitute x = 2y + 18 into (2)

5(2y + 18) = - 3y - 27

10y + 90 = - 3y - 27 ( add 3y to both sides )

13y + 90 = - 27 ( subtract 90 from both sides )

13y = - 117 ( divide both sides by 13 )

y = - 9

substitute y = - 9 into (1)

x = 2(- 9) + 18 = - 18 + 18 = 0

solution is (0, - 9 )

User Zeshan Munir
by
4.1k points